Intratemporal Nonseparability Between Housing and Nondurable Consumption: Evidence from Reinvestment in Housing Stock - Natalia Khorunzhina (Copenhagen Business School (CBS), Department of Economics, 2019)
Using the data on maintenance expenditures and self-assessed house value, I separate the measure of individual housing stock and house prices, and use these data for testing whether nondurable consumption and housing are characterized by intratemporal nonseparability in households' preferences. I find evidence in favor of intratemporal dependence between total nondurable consumption and housing. I reach a similar conclusion for some separate consumption categories, such as food and utility services. My findings also indicate households are more willing to substitute housing and nondurable consumption within a period than to substitute composite consumption bundles over different time periods.
hdl:10398/9729
Keywords: C51; D12; D13; E21; R21; 330; Intratemporal Nonseparability; Housing; Nondurable Consumption